New Developments in the Psychological Management of Chronic Pain - Morley, Stephen (Can J Psychiatry, 2015)
After reviewing how psychological treatment for chronic pain comes to have its current form, and summarizing treatment effectiveness, we explore several areas of development. We describe third wave therapies, such as mindfulness; we discuss what the research literature aggregated can tell us about what trials are more useful to conduct; and we outline some areas of promise and some failures to deliver on promise. The article is drawn together using the framework of the normal psychology of pain, identifying some of its most important implications for improving life for people with chronic pain.